मराठी

From the Sum of 3x − Y + 11 and − Y − 11, Subtract 3x − Y − 11. - Mathematics

Advertisements
Advertisements

प्रश्न

From the sum of 3x - y + 11 and - y - 11, subtract 3x - y - 11.

उत्तर

(3x - y + 11) + (- y - 11)

= 3x - y + 11 - y - 11

= 3x - y - y + 11 - 11

= 3x - 2y

(3x - 2y) - (3x - y - 11)

= 3x - 2y - 3x + y + 11

= 3x - 3x - 2y + y + 11

= -y + 11

shaalaa.com
  या प्रश्नात किंवा उत्तरात काही त्रुटी आहे का?
पाठ 12: Algebraic Expressions - Exercise 12.2 [पृष्ठ २४०]

APPEARS IN

एनसीईआरटी Mathematics [English] Class 7
पाठ 12 Algebraic Expressions
Exercise 12.2 | Q 6.1 | पृष्ठ २४०

व्हिडिओ ट्यूटोरियलVIEW ALL [1]

Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×